2020
DOI: 10.1021/acs.iecr.0c02605
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Kraft Lignin Solubility in Protic Ionic Liquids and Their Aqueous Solutions

Abstract: In this study, the potential of alkanolammonium-based protic ionic liquid (PIL) aqueous solutions as solvents of Kraft lignin was evaluated. The results showed that the PILs' anion plays a key role in lignin dissolution, while the cation plays a secondary role. The presence of extra hydroxyl groups in the anion structure negatively affects lignin solubility, while the increase of the cation alkyl chain favors this process. Using mechanical agitation, all tested PILs required 8 h to reach saturation, except for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 66 publications
(138 reference statements)
0
11
0
Order By: Relevance
“…As another alternative, ionic liquid is proven to be a good solvent for lignin and even lignocellulose. For example, Dias et al [58] . reported the solubility of Kraft lignin in solvents of alkanol ammonium‐based protic ionic liquids (PILs) aqueous solutions.…”
Section: Current Techniques For Reducing the Diffusion Limitationsmentioning
confidence: 99%
“…As another alternative, ionic liquid is proven to be a good solvent for lignin and even lignocellulose. For example, Dias et al [58] . reported the solubility of Kraft lignin in solvents of alkanol ammonium‐based protic ionic liquids (PILs) aqueous solutions.…”
Section: Current Techniques For Reducing the Diffusion Limitationsmentioning
confidence: 99%
“…On the other hand, reducing the kraft lignin molecular weight by solvent fractionation can enhance its miscibility and dispersion in the PU matrix, and consequently can improve some properties of the resulting PU such as the mechanical properties [ 115 ]. The use of binary organic solvent mixtures such as acetone–methanol [ 116 ], aqueous two-phase systems (ATPSs) composed of (NH 4 ) 2 SO 4 and ethanol [ 117 ], and the use of ionic liquids [ 118 ] are examples of strategies used to reduce the molecular weight of lignin as well as its heterogeneity. However, it is important to take into account that commercializing low-molecular-weight lignin has been economically unfeasible until now.…”
Section: Lignin As a Building Block To Synthesize Polyurethanesmentioning
confidence: 99%
“…In 2009, it was found that cellulose-rich material can be obtained in a single step via the complete dissolution of softwood and hardwood in the ionic liquid 1-ethyl-3-methylimidazolium acetate followed by separation [152]. Currently, there are multiple ILs for the dissolution, pretreatment, and/or processing of biopolymers and biomasses (chitin/chitosan [153], silk fibroin [154], lignin [155], starch [156], keratin [157], etc.). The most efficient anions used in ILs for cellulose dissolution are basic ones such as chloride (Cl − ), carboxylates (e.g., acetate ([OAc] − ), formate ([HCOO] − ), and propionate ([OPr] − )) or derivatives of mineral acids (e.g., diethylphosphate ([(EtO) 2 PO 2 ] − ) and dimethylphosphate ([(MeO) 2 PO 2 ] − ) [158]).…”
Section: Ionic Liquids (Ils)mentioning
confidence: 99%